Autonomic Neuropathy in Young Asymptomatic Type 2 Diabetics - A Rural Based Indian Study - Kaveri N Karewad (Al Ameen Journal of Medical Sciences, 2020)
Aims: To evaluate autonomic functions in young diabetics without any symptoms and signs of autonomic neuropathy and compare the same with young non diabetics. Materials Method: It is a prospective observational study, done at Sree Sidhi Vinayaka Diabetic Center, during July to December 2017. Autonomic function tests were done on young diabetics without symptoms or signs of autonomic dysfunction [Group A] and compared same with young age matched non diabetics [Group B]. Result: A total of 84 participants were included in the study having 48 patients [Group ‘A’], and 36 subjects [Group ‘B’]. The mean age of the patient in Group A 35.33 ± 3.76 and Group B 34.61 ± 3.68 [p-value 0.90] with male to female ratio of 2.81: 1 [male preponderance]. A statistically significant variation was found in Resting Heart Rate, Heart Rate Variation to deep breathing, Valsalva Ratio, Postural Fall of SBP, Rise in DBP on Sustained Hand Grip [p<0.01]. Conclusion: Impaired autonomic neuropathy is associated with development of diabetes and autonomic denervation is evident even before diagnosis of diabetes.